2008
DOI: 10.2215/cjn.00030108
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Outcomes in the Outpatient Kidney Transplant Clinic

Abstract: Background and objectives: Cardiovascular disease is an important cause of morbidity and death in kidney transplant recipients. This study examines the Framingham risk score's ability to predict cardiac and stroke events. Because cyclosporine and tacrolimus have different cardiovascular risk profiles, these agents were also examined.Design, setting, participants, & measurements: A prospective cohort evaluation of 540 patients were followed for a median of 4.7 yr in an outpatient kidney transplant clinic. Basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 35 publications
(43 reference statements)
2
43
1
1
Order By: Relevance
“…86 A prospective cohort evaluation of 540 prevalent transplant recipients enrolled at average of 6.6 years after transplantation and followed up for an average of 4.7 years found that the ratio of observed to predicted cardiac events based on the FHS was 1.64 for the cohort overall. 87 Observed cardiac events rates exceeded FHS predictions in patients with pretransplantation diabetes mellitus and those with prior cardiac disease, being 2.74 times the predicted risk in patients 45 to 60 years of age with prior cardiac disease or diabetes mellitus. 87 However, observed risk did not exceed predictions in older patients considered without regard to comorbidity or in younger patients free of prior diabetes mellitus or cardiac history.…”
Section: Considerations For Kidney Transplantation Candidates With DImentioning
confidence: 76%
See 1 more Smart Citation
“…86 A prospective cohort evaluation of 540 prevalent transplant recipients enrolled at average of 6.6 years after transplantation and followed up for an average of 4.7 years found that the ratio of observed to predicted cardiac events based on the FHS was 1.64 for the cohort overall. 87 Observed cardiac events rates exceeded FHS predictions in patients with pretransplantation diabetes mellitus and those with prior cardiac disease, being 2.74 times the predicted risk in patients 45 to 60 years of age with prior cardiac disease or diabetes mellitus. 87 However, observed risk did not exceed predictions in older patients considered without regard to comorbidity or in younger patients free of prior diabetes mellitus or cardiac history.…”
Section: Considerations For Kidney Transplantation Candidates With DImentioning
confidence: 76%
“…87 Observed cardiac events rates exceeded FHS predictions in patients with pretransplantation diabetes mellitus and those with prior cardiac disease, being 2.74 times the predicted risk in patients 45 to 60 years of age with prior cardiac disease or diabetes mellitus. 87 However, observed risk did not exceed predictions in older patients considered without regard to comorbidity or in younger patients free of prior diabetes mellitus or cardiac history.…”
Section: Considerations For Kidney Transplantation Candidates With DImentioning
confidence: 76%
“…However, kidney transplant recipients with diabetes have a higher mortality than those without diabetes because of their elevated risk of cardiovascular complications and infectious complications [2, 3]. Several reports demonstrated that recipients with diabetes had a higher frequency of cardiovascular events and deteriorated patient survival rates [3, 23]. Four patients enrolled in this study had cardiovascular disease before transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In kidney transplants, 2 different studies have demonstrated that the Framingham model, which estimates the 10-year risk of fatal and nonfatal coronary event, did not predict absolute ischemic heart disease in the transplant population, particularly in high riskpatients. 25,26 In liver transplant, only 1 study from Germany has performed an external validation of 3 different scores and has demonstrated that SCORE and PROCAM can discriminate liver transplant recipients for their individual risk of cardiovascular events, whereas the Framingham score did not. 27 Neal and associates reported that the predicted 10-year risk of coronary heart disease according to Framingham equation increased from 6.9% before transplant to 11.5% at 1 year after transplant, whereas that of a matched local population was 7%.…”
Section: Olivier Guillaud Et Al /Experimental and Clinical Transplantmentioning
confidence: 99%
“…Given they have been developed in the general population, they underestimate the real risk in high-risk groups such as diabetic patients, patients with advanced chronic renal failure, and patients with prior history of cardiovascular events. 26,32,33 Besides, they are not validated in young and/or older populations. For instance, the SCORE system is only recommended for use in a 40-to 65-year age range, 6 so 29% patients of our cohort were not eligible.…”
Section: Olivier Guillaud Et Al /Experimental and Clinical Transplantmentioning
confidence: 99%